Unusual Lymph Node Metastases of Prostate Cancer Detected by 18F-Fluorocholine PET/CT. (April 2015) - Pinaquy, JB; Allard, JB; Cornelis, F; Pasticier, G; De Clermont, H
<x xml:space="preserve">Abstract</x> Abstract A 65-year-old patient with prostate adenocarcinoma was explored by 18F-fluorocholine (FCH) PET/CT for pretreatment staging because of a high risk of prostate cancer. Images showed multiple foci with increased uptake of 18F-FCH within some pelvic and retroperitoneal lymph nodes, osseous foci (iliac bones and sacrum), and much more unusual, increased uptake foci within some left supraclavicular and left axillary lymph nodes. Owing to the rarity of spread to supraclavicular lymph nodes, surgical removal was performed and revealed prostate cancer metastases.